PERAN GURU AGAMA ISLAM DALAM MENGATASI KESULITAN PESERTA DIDIK DALAM MEMBACA AL QUR'AN DI SMA AL-RIFA'IE GONDANGLEGI - Ulva Azizah Azzuhro; Rosichin Mansur; Ika Anggraheni (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Reading the Qur'an is certainly an activity that will not be unfamiliar and even often done.But in this age of globalization, there are many shifts in values in people's lives because there are still many generations who have not been able to read the Qur'an. From the background above, the researcher formulated a problem, namely about the difficulties of students in reading the Qur'an, the teacher's method of overcoming the difficulties of students in reading the Qur'an and the results of the teacher overcoming the difficulties of students in reading the Qur'an. This research was conducted at Al-Rifa'ie Gondanglegi High School and using this type of research is a case study using a qualitative approach. The data collection procedure is carried out using the observation method. The conclusions of this study include, among others, the difficulties of students in reading the Qur'an there are 3 kinds: (1) Difficulty understanding Makharijul Letters (2) Difficulty understanding the application of tajwid science in the Qur'an (3) Difficulty understanding changes in the shape of hijaiyyah letters that are connected with other letters. Then the method used by the teacher in overcoming the difficulty of reading uses the Iqro' method and the results of this method students have begun to be able to apply to the Qur'an.